RECONSTRUCTION OF BOARDING SCHOOL CURRICULUM - Munawir - Yusuf (Pondok Pesantren Modern Islam Assalaam, 2017)
The curriculum is a set of plans and arrangements concerning objectives, content, and instructional materials and ways used as guidelines for the implementation of learning activities to achieve specific educational goals. PPMI Assalaam’s curriculum is a blend of Islamic ideology with the demands of society and the demands of change. The academic problem that arises is the demand for continuous evaluation of the curriculum used in boarding school environment so that it can be in tune with the development of the times and the development of the demands of society. Development of PPMI Assalaam Curriculum must consider three things (1) ideology of boarding school establishment, (2) aspirations and expectations of stake hoders, and (3) demands of the times. Looking at the current structure of PPMI Assalaam curriculum, taking into account various issues, reconstruction is needed to meet the expectations of all parties. The combination of the formal education curriculum with the curriculum of the boarding school is one of the curriculum’s cores that should be done in the assessment. Likewise too heavy learning load, the number of subjects that are too many, will have implications on the needs of large human resources. In the future the reconstruction of the PPMI Assalaam curriculum should start from the objectives, content / process, and evaluation.